STRUKTUR MUSIK KABAWATN DALAM ACARA RITUAL BALLENGANG DI DESA SAHAN KECAMATAN SELUAS KABUPATEN BENGKAYANG - Adventinus rickardo sr; Nurmila Sari Djau; Asfar Munir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe background of this research is the uniqueness of Kabawan't music in the Balenggang ritual, besides that the researcher's concern is in local culture, so that the Balenggang ritual, especially Kabawant music, can be documented and known by the younger generation. The purpose of this study is to describe the analysis of the structure of Kabawat'n music in the balenggang ritual event in the village of Sahan, a sub-district covering an area of Bengkayang district.The method used in this research is an explorative descriptive method. The form of this research is qualitative.This research uses a musicological approach. The data collection technique of this research is observation, direct communication. Checking the validity of research data used triangulation techniques, increasing the persistence and length of observations.The result of this research is Kabawant music is music used to accompany the balenggang ritual. The Kabawat'n music in this balenggang ritual is simple and monoton, the musical instruments used are dau induk, dau anak, tuma, tawa and gong. The results of this analysis can be implemented in school learning in the form of a design implementation of the Kabawat'n music structure in the balenggang ritual event in the seventh grade junior high school cultural arts subject with competency standards according to the traditional music background in the cultural context of the local community.Keywords: Kabawat'n music structure in the balenggang ritual